FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KESELAMATAN BERKENDARA PADA PEKERJA DI KECAMATAN TANJUNG PRIOK TAHUN 2023 - Handoko (2023)
Safety riding behavior is an ideal behavior that must be applied by any workers to increase the worker's safety and other road users. There has been an increased prevalence and mortality rate due to traffic accidents in 2022. This research aims to determine the factors associated with safety riding behavior among workers in Tanjung Priok District in 2023. A total of 112 workers calculated by using Lemeshow formula were selected by a proportionate stratified sampling technique. The research design was cross-sectional and data were analyzed by chi-square test. The finding showed that factors associated to safety riding behavior were knowledge (p-value = 0,001), attitude (p-value = 0,007), driving's PPE (p-value = 0,010), driving insurance ownership (p-value = 0,046), and family support (p-value = 0,001). Meanwhile, the type of work factor (p-value = 0,247) had no association with safety riding behavior. Local government is required to cooperate with the police departement to increase worker's knowledge about how to operate their vehicle and equipment so safety riding behavior is formed.